Study of Sodium Chloride Production Using Gradual Evaporation of Seawater from Nggolonio Sea, East Nusa Tenggara - Ernesta Wae; Rachmat Triandi Tjahjanto; Diah Mardiana (Chemistry Department, The University of Brawijaya, 2021)
Sea water as a raw material resources for the kitchen salt production, besides containing NaCl, has also containing other dissolved salts such as hygroscopic calcium and magnesium salts. The high content of other salts cause industrial NaCl has a low quality. This aim research was to find out the effect of seawater evaporation on NaCl content changes. Seawater obtained from Nggolonto, Nagekeo, NTT, was used with an initial volume of 200 mL, then it was concentrated in varying of final volume, i.e. 20, 23, 25, 27 and 29 mL. The NaCl content was calculated based on total chloride ion content, corrected toward magnesium and calcium ions content and the presence of sulphate anion. In addition, the chloride and magnesium also calcium ions content was analyzed volumetrically, while the sulphate anion was determined spectrophotometrically. The research result showed that NaCl content increase significantly up to 27 mL of final volume and was constantly afterward. Furthermore, the highest of NaCl content obtained from final volume of 29 mL was 96.01%. Nevertheless, comparing to SNI 06-0303-1989, its content was still below the standard of 98.5%.